Role of beta-stabilizing elements on the microstructure and mechanical properties evolution of modified PM Ti surfaces designed for biomedical applications. (15th March 2018) - Ureña, J.; Tejado, E.; Pastor, J. Y.; Velasco, F.; Tsipas, S.; Jiménez-Morales, A.; Gordo, E.
ABSTRACT: This work focuses on the evaluation of modified surfaces on Ti produced by powder metallurgy. These newly designed surface modifications are achieved by deposition and diffusion of a stable aqueous suspension prepared in one case from micro-sized Nb powder (Ti β-stabilizer element) and in another case from Nb plus the addition of ammonium chloride, NH4 Cl, (thermo-reactive diffusion process). Different design parameters such as diffusion element (Nb or Mo), state of the Ti substrate (green or sintered) and the treatment process (diffusion or thermo-reactive diffusion) lead to all the surface-modified materials, GreenTi–Nb, SintTi–Nb and Ti–NbNH4Cl, GreenTi–Mo, SintTi–Mo and Ti–MoNH4Cl . The modified Ti surfaces present a gradient in composition and microstructure (β / α+β / α phases) resulting in an improvement in some of their mechanical properties: (1) higher micro-hardness in all the modified materials and (2) lower elastic modulus (more similar to that of the human bone) in those without NH4 Cl. Invited keynote papers from EuroPM2017, Milan.